The Influence of Online Advertising and Perceived Usefulness and Its Impact on Actual Use through Payment Intention among ShopeePay E-Wallet Users - Permanasari, Kartika Indah; Azzuhri, Fahmi Muhammad; Asmar, Asmar; Salam, Rudi (Universitas Negeri Makassar, 2024)
This study aims to identify and explain whether there is an influence of online advertising on payment intention and actual use among ShopeePay e-wallet users, to determine whether perceived usefulness affects payment intention among ShopeePay users, and whether online advertising influences perceived usefulness among ShopeePay e-wallet users. Additionally, it seeks to identify and explain whether there is an effect of payment intention on actual use among ShopeePay e-wallet users, and whether perceived usefulness affects actual use of ShopeePay. The methodology involves 250 respondents who use ShopeePay, have seen online advertisements, and are between the ages of 15 to 50. The results indicate that online advertising significantly influences perceived usefulness, and has a significant effect on payment intention and actual use. Likewise, perceived usefulness significantly influences both payment intention and actual use. These findings support previous research on the antecedents of advertising attitudes in the context of social media, confirming that online advertising influences product evaluation, and reinforcing that advertising attitude, product evaluation, and incentives are important factors in determining consumer purchase intentions. Practical implications—these findings are crucial for advertising marketing managers. Online advertising on credible social media platforms and apps increases consumers' purchasing intentions. Advertisers should build a good reputation for the online advertisements they broadcast.